(untitled) (Revista Educação, Artes e Inclusão, 2025)
Abstract The objective of this work is to present a proposal for a pedagogical intervention on the importance of developing ethical awareness within the context of technical training in the food course. At first, we introduce ethics and approach the problem of an education thought through a purely technical bias and its impacts on the training of future technicians. In the second moment, we present the death of critical reason and the emergence of instrumental reason. For Adorno and Horkheimer, the advancement of technical knowledge, as an expansion of the horizon of human thought activity, is linked to a reduction in the criticality of individuals and, consequently, to a process of dehumanization and deterioration of an ethical conscience. Making a parallel between the thinkers Theodor Adorno, Max Horkheimer and Paulo Freire, we try to show that it is important to think about professional education linked to a philosophical reflection that enables the construction of an ethical conscience that is capable of making future technicians fight the process of dehumanization and diminution of ethics within a capitalist society dominated by a technicist notion of education. Keywords: technique; ethic; consciousness; instrumental reason; pedagogical intervention.